Seasonality of Violet-winged grasshopper (Tropidacris collaris) (Stoll, 1813) (Orthoptera: Romaleidae) in the dwarf cashew - de Sousa Maciel, Gabriela Priscila; de Lima Farias, Lucas; Lhano, Marcos Gonçalves; Malaquias, José Bruno [UNESP]; Duarte, Poliana Martins; Silva, Marcos Levi Saraiva; da Silva Dias-Pini, Nivia (Southern Cross Publishing, 2023)
Tropidacris collaris (Stoll, 1813) is a polyphagous pest, found throughout the South American continent.It has recently been reported to cause damage to cashew trees. The aim of this study was to evaluate the population dynamics of T. collaris in the dwarf cashew, the effects of climate variables on the population dynamics of T. collaris, and the population dynamics of T. collaris in relation to the phenological stages of the dwarf cashew. Violet-winged grasshopper was collected in a clonal garden with 35 dwarf cashew clones (Anacardium occidentale L.) in Pacajus, Ceará, Brasil. The specimens were randomly captured using an entomological net in two collectors spaced 10 m apart. The collections were made between 09:00 and 11:00, in two 45-min shifts separated by an interval of 15 min. In the laboratory, the insects were separated and weighed, and the females dissected to assess the degree of maturation of the ovaries (I, II and III) and classify the ovipositor valves. A greater abundance of adults was found in December 2017 and June 2018. The number of females with mature ovaries (type III) showed a positive correlation with ovipositors with open valves, such ovaries being registered in December 2017, and in January and July 2018. Wind speed, evapotranspiration and relative humidity showed a significant correlation with the nymph population of T. collaris. The greatest peaks in the nymph population were stimulated by the leaf fall/leaf flux phenological stages of the dwarf cashew. In this study we show some of the phenological aspects of T. collaris under field conditions, correlated with climatic and phenological variables of the cashew tree. These results may help in decision-making about the application of methods to control T. collaris in tropical regions, as this insect is polyphagous, and its large size has great potential for damage to several crops.
Keywords: abiotic factors; Anacardium occidentale; behavior; giant grasshopper; population dynamics